KELAYAKAN SCRAPBOOK SUB MATERI PEMANFAATAN KEANEKARAGAMAN HAYATI INDONESIA - Uray Rina Septiani; Laili Fitri Yeni; Reni Marlina (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2020)
This research aimed to determine the student learning outcomes with cooperative learning models assisted by flipbook media in the material of the human motion system in class VIII SMP Negeri 14 Pontianak. The form of this research was quasi-research (Quasy Experimental Design) with the research design used was Non-equivalent Control Group Design. The research sample was class VIII I as an experimental class and VIII H as a control class, with intact group sampling techniques. The instruments used were multiple choice tests totaling 20 questions. The average student learning outcomes in the experimental class was 16.54, while in the control class was 15.52. The results of the Mann Whitney U test analysis showed that the value of Zhitung<-Ztabel is -2.40 <-1.96, then Ho was rejected and Ha was accepted, meaning that there were differences in learning outcomes of students taught using cooperative learning models assisted by flipbook media and students who are taught using conventional learning models. The value of the effect size was obtained by 0.72 with the medium category, giving an effect of 26.42% on the learning outcomes of students in human motion system material in class VIII of SMP Negeri 14 Pontianak.